Plan estratégico y su incidencia en el desarrollo institucional de la unidad educativa El Empalme, cantón El Empalme, periodo 2015-2019 - Pisco Zambrano, Karolina Stefany (2016)
This research has as its main objective. The development of a strategic plan for the institutional development of the Education Unit El Empalme, to which different surveys of students, teachers, and an interview to the authorities took place, before this information could be obtained regarding the current situation the institution, its main strategic goals and aspirations; once it is known the above could set a strategic plan with its main activities and goals, as well SWOT analysis, which yielded information on the strengths, weaknesses, opportunities and threats was set also could raise the strategic priorities, mission, vision, values plus the necessary expenses, established within the budget. Mostly teachers of the Education Unit El Empalme, are willing to participate in the change process and to cooperate with the institutional philosophy, established in the strategic plan, it should also be noted that students are committed to this process and They collaborated with embodied ideas within the strategies established in the plan. Kaywords: Strategic Plan, Institutional Development, Current Status, Objectives, Strategies, Foda, Mission, Vision, Institutional Philosophy.